Physiotherapy intervention for rotator cuff syndrome: a case study report - Rosadi, Rakhmad; Wardojo, Sri Sunaringsih Ika; Rahmanto, Safun; Yuliadarwati, Nungki Marlian (International Journal of Research in Medical Sciences, 2022)
This research was motivated by the general complaints that patients generally experience functional disorders, patients found it difficult to wear their own clothes, comb their hair and carry heavy items or activities due to repetitive and chronic excessive shoulder. This is because in patients with rotator cuff syndrome, they feel pain which can cause limitation of joint motion in the shoulder, thereby reducing muscle strength and reducing functional activity. Purpose of this study was to determine the result of physiotherapy intervention given towards reducing pain and improve the disability index for patients with rotator cuff syndrome This research uses descriptive analysis method. The method of data collection using the autoanamnesis method. The research design used is a case study with the subject of this research being a patient with a diagnosis of shoulder sprain rotator cuff syndrome using ultrasound, tens and exercise therapy modalities. To find out the benefits of giving ultrasound, tens and exercise therapy to rotator cuff syndrome on pain, spasm, limitation of motion, muscle strength and functional activity.